2022
DOI: 10.3390/ijerph19031365
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biodegradation of Phenylurea Herbicides by Ochrobactrum anthrophi CD3 Assessment of Its Feasibility in Diuron-Contaminated Soils

Abstract: The phenylurea herbicides are persistent in soil and water, making necessary the de-velopment of techniques for their removal from the environment. To identify new options in this regard, bacterial strains were isolated from a soil historically managed with pesticides. Ochrobactrum anthropi CD3 showed the ability to remove completely herbicides such as diuron, linuron, chlorotoluron and fluometuron from aqueous solution, and up to 89% of isoproturon. In the case of diuron and linuron, their main metabolite, 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Another possibility could be that RAMEB was also acting as a biostimulant for the soil microbiota activity. This fact has been previously demonstrated for other CDs [25,30,[63][64][65]. Although RAMEB is considered a poorly biodegradable CD [66], Fava et al [67] observed that aerobic microorganisms isolated from polychlorinated-biphenyls-contaminated soil were able to metabolise RAMEB as only carbon and energy source.…”
Section: Discussionmentioning
confidence: 59%
“…Another possibility could be that RAMEB was also acting as a biostimulant for the soil microbiota activity. This fact has been previously demonstrated for other CDs [25,30,[63][64][65]. Although RAMEB is considered a poorly biodegradable CD [66], Fava et al [67] observed that aerobic microorganisms isolated from polychlorinated-biphenyls-contaminated soil were able to metabolise RAMEB as only carbon and energy source.…”
Section: Discussionmentioning
confidence: 59%
“…Some bacteria capable of degrading diuron and linuron to mono- or dichloroaniline, such as 34DCA and 4-chloroaniline, have been reported [ 5 , 6 , 7 ]. Sphingomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the characterization of mono-and dichloroaniline biodegradation is important for the remediation of environments contaminated by phenylurea herbicides. Some bacteria capable of degrading diuron and linuron to mono-or dichloroaniline, such as 34DCA and 4-chloroaniline, have been reported [5][6][7]. Sphingomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…Hathout et al, ( 2022 ) data revealed that agricultural soil samples from Egypt governorates were highly contaminated (from 10 to 80%) by different pesticide residues. Many researchers have reported that IPU has deleterious effects on microbial communities and is carcinogenic for animals and humans (Vallotton et al 2009 ; Alba et al 2022 ). The IPU is documented to induce oxidative stress that results in the damage of proteins, lipids, and other cellular components, thus inhibiting growth or leading to organism death (Rutherford and Krieger-Liszkay 2001 ).…”
Section: Introductionmentioning
confidence: 99%